AUGMENTED PROSTAGLANDIN E2 SIGNALING CAUSES PODOCYTE DAMAGE AND ALBUMINURIA-LIKE PHENOTYPE IN A ZEBRAFISH DISEASE MODEL OF GLOMERULAR HYPERFILTRATION. (June 2022) - Kourpa, Aikaterini; Mangelsen, Eva; Bolbrinker, Juliane; Schulz, Angela Martina; Rothe, Michael; Kreutz, Reinhold; Panakova, Daniela
Abstract : Objective: Prostaglandins (PGs) are important active lipids synthesized from arachidonic acid with the participation of cyclooxygenases (COXs) and specific prostaglandin synthases. Prostaglandin E2 (PGE2), the most abundant prostaglandin in the kidney, plays a crucial role in renal homeostasis and the pathogenesis of chronic kidney diseases. Augmented PGE2 signaling that may occur in podocytes during increased fluid flow shear stress as observed during glomerular hyperfiltration, results in glomerular filtration barrier (GFB) permeability defects, ultimately leading to albuminuria. The cellular mechanisms that precede podocyte damage are not fully resolved. Here, we deploy a zebrafish model to study the role of PGE2 signaling in glomerulus and its effects on GFB integrity and function. Design and method: To model the outcome of increased PGE2 signaling in podocytes, zebrafish embryos were exposed to 16, 16-dimethyl PGE2 (dmPGE2, 125 μM) or DMSO vehicle after the complete formation of GFB, i.e. from 72 hours post fertilization (hpf) to 96 hpf. To probe the PGE2 pathway, embryos were treated with the selective PGE2 receptor (EP) type 2 (EP2) and EP4 antagonists PF04418948 and ONO-AE3-208 or the COX inhibitor indomethacin. Zebrafish embryos of Tg(fabp10a:gc-EGFP) were used to evaluate the functional role of GFB integrity and albuminuria phenotype, while embryos of Tg(wt1b:EGFP) in combination with angiography using BSA-conjugated AlexaFluor555 allowed glomerular morphological analysis. In vivo stereomicroscopy, confocal laser scanning microscopy, and electron microscopy were used to analyze GFB at cellular as well as ultrastructural level. Statistical analysis was performed using GraphPad software. Results: Stimulation with dmPGE2 causes an albuminuria-like phenotype in zebrafish embryos, mimicking the suggested PGE2 effects during glomerular hyperfiltration in rodent models. The albuminuria-like phenotype could be significantly suppressed by the combined and separate inhibition of the EP2 and EP4 receptors as well as by indomethacin treatment. Although the glomerular ultrastructure appeared unaffected, high-resolution confocal imaging showed impaired podocyte intercalation around the glomerular capillaries after dmPGE2 exposure. Importantly, these specific podocyte defects were restored after blockage of EP2 and EP4. Conclusions: Our results support a role of augmented PGE2/EP2/EP4 signaling in the setting of glomerular hyperfiltration and albuminuria.